Peran Penting Sel T Regulator CD8+CD25+FOXP3+ Menjaga Homeostasis Sel T pada Transplantasi Alogenik (ESSENTIAL ROLES OF CD8+CD25+FOXP3+ REGULATORY T CELLS IN THE MAINTENANCE OF T CELLS HOMEOSTASIS IN ALLOGENEIC TRANSPLANTATION) - Rifa’i, Muhaimin; Soewondo, Aris (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
Tolerance between donor and recipient is a key for successful allogeneic transplantation. To determinethe involvement of CD8+ T cells in regulating T cell homeostasis in allogeneic transplantation, spleen cellswere analyzed post bone marrow transplantation. In this study, C57BL/6 mice were used as donor andBALB/c mice were used as recipients. BALB/c mice were irradiated with a lethal dose of 850 rad prior tothe transplantation. Twenty-four hours post a radiation BABL/c mice were transplanted with bone marrowcells (10x106) derived from C57BL/6 mice that free from mature T cells. Analysis of hematopoietic cells inthe spleen was done two months post-transplantation. The results showed that CD8+CD25+FOXP3+ T cellin collaborasion with CD4+ regulatory T cell contribute to the prevention of graft-versus-host diseases(GVHD). In this study at was demonstrated that naïve CD4+CD62L+ T cells dominated the sub set of Tcells, whereas the development of CD4+CD44+ memory T cells are very limited. In conclusion, that regulatoryT cells maintain normal homeostasis by maintaining T cells remained at naïve status.
Keywords: CD8+CD25+FOXP3+, allogeneic transplantation, Treg